KONTRIBUSI PENGETAHUAN DAN SIKAP MAHASISWA D III KEPERAWATAN DI PEKANBARU TENTANG RESPON TIME TRIAGE SEBELUM PRAKTEK KLINIK DI RUANG GAWAT DARURAT TAHUN 2018 - Putri Wulandini, Andalia Roza, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The knowledge, attitudes and abilities of IGD personnel are indispensable in makingdecisions that are not possible in sorting out during triage in more optimal and targetedsituations. Diploma nursing students are the most students who are internships inhospitals, be they government hospitals and non government education hospitals. One ofthe rooms entered by this nursing student is an emergency unit. This study aims todetermine the relationship of knowledge and attitudes of the students of D III of Nursing inPekanbaru on the response time triage before the clinic practice in the emergency room.This research uses quantitative research type with cross sectional research design. Thesample of this research is D III student of Nursing which will be done clinic practice inemergency room in Pekanbaru city with the number of 171 students. The samplingtechnique used is total sampling using inclusion and exclusion criteria. Instrument whichis knowledge and attitude about triage response time. Data processing includes editing,coding, processing, cleaning, and tabulating. Analysis of univariate and bivariate analysisdata with the help of SPSS. The result of the research was obtained by good knowledge asmany as 120 students (70.2%) and poor knowledge as many as 51 students (29.8%); goodattitude as many as 97 students (56.7%) and bad attitude as many as 74 students (43.3%);and there is a significant relationship between knowledge and attitude with p-value 0,00.Suggestions for educational users to further motivate learners to learn more about triageresponses in order to avoid triangle selection.Keywords: Triage response time, knowledge, attitude